Comparison of Pharmacological Treatment Effects on Long-Time Outcomes in Heart Failure With Preserved Ejection Fraction: A Network Meta-analysis of Randomized Controlled Trials - Lin, Yaowang; Wu, Meishan; Liao, Bihong; Pang, Xinli; Chen, Qiuling; Yuan, Jie; Dong, Shaohong (Frontiers in Pharmacology, 2021)
Beneficial effects of therapeutic drugs is controversial for heart failure with preserved ejection fraction (HFpEF). This meta-analysis aimed to evaluate and compare the interactive effects of different therapeutic drugs and placebo in patients with HFpEF. A comprehensive search was conducted using PubMed, Google Scholar, and Cochrane Central Register to identify related articles published before March 2021. The primary outcome was all-cause mortality. Secondary outcomes were cardiovascular mortality, heart failure (HF) hospitalization, and worsening HF events. A total of 14 randomized controlled trials, comprising 19,573 patients (intervention group, n=9,954; control group, n=9,619) were included in this network meta-analysis. All-cause mortality, cardiovascular mortality, and worsening HF events among therapeutic drugs and placebo with follow-up of 0.5–4 years were not found to be significantly correlated. The angiotensin receptor neprilysin inhibitor (ARNI) and angiotensin-converting enzyme inhibitor (ACEI) significantly reduced the HF hospitalizations compared with placebo (hazard ratio [HR] 0.73, 95% confidence interval [CI] 0.60-0.87 and HR 0.64, 95% CI 0.43-0.96, respectively), without heterogeneity among studies. The ARNI was superior to angiotensin receptor blocker (ARB) in reducing HF hospitalizations (HR 0.80, 95% CI 0.71-0.91), and vericiguat 10 mg ranked worse than beta-blockers for reducing all-cause mortality in patients with HFpEF (HR 3.76, 95% CI 1.06-13.32). No therapeutic drugs can significantly reduce mortality, but the ARNI or ACEI is associated with the low risk of HF hospitalizations for patients with HFpEF.